DI-057 Biological treatment and psoriasis: the correlation between clinical efficacy and therapeutic adherence. (24th February 2014) - Marletta, E; Spadaro, D; Sgarlata, D; Guzzardi, S; Avola, N; Regolo, S; Valerio, A; Cacciaguerra, G
Abstract : Background: Psoriasis is a chronic disease that significantly affects patients' quality of life (QoL). Biological drugs interfere in the immunological processes that trigger and support psoriasis and, therefore, prove effective in its treatment. Purpose: To analyse the adherence, tolerability and the short- and long-term effectiveness of biological drugs in patients with moderate to severe plaque psoriasis. To evaluate how the increase in QoL perceived by the patient can be related to treatment adherence and remission of the disease. Materials and methods: Retrospective study of all the patients with psoriasis treated with biological drugs from March 2012. Clinical efficacy in the treatment was determined by the Psoriasis Area Severity Index (PASI) and the Dermatology Life Quality Index (DLQI) scores before and during the treatment. To calculate the adherence we used a record of prescriptions dispensed over a period of six months. We used the formula:% adherence = n. of units dispensed/n. of units theoretically needed ×100. Results: 41 treatment-naive patients, 64.2% men. Administered drugs were: ustekinumab (78%) adalimumab (17%) and etanercept (5%). 25 patients achieved least 75% improvement (PASI75) in the disease between weeks 12–18 of treatment; 15 patients had already reached PASI75 within 12 weeks. The median baseline DLQI score was 16.97 and the median DLQI score during the treatment was 1.34. No patients developed significant adverse reactions to the treatment (1% headache, 5% temporary redness at the injection site) and there was only one therapeutic switch (for lack of efficacy). The adherence was very high: 82% of patients had adherence > 95%, 17% adherence between 60% and 80% and only 1% <60%. Conclusions: The biological drugs demonstrated rapid onset of action and high effectiveness, safety and a great improvement in the quality of life in patients with moderate to severe plaque psoriasis. The therapeutic adherence was related to the increase of QoL. The involvement of the patient is essential for cost-effective management of disease. No conflict of interest.